2010
DOI: 10.1002/adem.201080051
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Cellular Response of Novel Hybrid Network Structure Elastomers with Inorganic Short Chain Cross‐Links for Soft Tissue Reconstruction

Abstract: The flexible and highly ductile silicone elastomer widely used as a soft‐tissue substitute for joint reconstruction and replacement fragments prematurely because of low tensile strength and inadequate bone build‐up around the implants. In this regard, an excellent vehicle to favorably modulate cellular response and retain intrinsic elastic recovery of soft tissue implants is to consider hybrid network structure elastomers with inorganic short chain cross‐links. The concept involves covalently linking nanocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The mechanism of action of active substance for antimicrobial activity has been reported by many researchers to be related to cellular mechanism. [41][42][43][44] The particular aspects of TiO 2 mechanism on microbes have also been reported in the literature. [45][46][47] Thus, the mechanism of the particle would be the interaction of the particle with the cellular membrane of the microbes and hence interfere with the metabolic action of microbes negatively leading to cellular distruction.…”
Section: Antimicrobial Screening For Fabricsmentioning
confidence: 96%
“…The mechanism of action of active substance for antimicrobial activity has been reported by many researchers to be related to cellular mechanism. [41][42][43][44] The particular aspects of TiO 2 mechanism on microbes have also been reported in the literature. [45][46][47] Thus, the mechanism of the particle would be the interaction of the particle with the cellular membrane of the microbes and hence interfere with the metabolic action of microbes negatively leading to cellular distruction.…”
Section: Antimicrobial Screening For Fabricsmentioning
confidence: 96%
“…Shah et al [57] reported hybrid networks in which acrylic acid was used as the crosslinker between titania and silicone. NCO groups could also be used as ac rosslinker [58] (Scheme 6).…”
Section: Ring-opening Polymerization(rop)mentioning
confidence: 99%
“…Moreover, the increase in annealing temperature significantly enhances the photocatalytic and antimicrobial performance, which are related to a decrease in the band gap energy of titania. [8][9][10][11][12][13][14][33][34][35][36][37][38]…”
Section: Optical Characterisationmentioning
confidence: 99%